Temporal-Eschatic Dimension of History. A Contribution to Historiological Considerations - Sołga, Przemysław (Sensus Historiae, 2021)
History as a science does not limit itself only to matters of the past and, in a similar manner, eschatology does not focus only on futuristic implications. This text touches upon theological issues, especially eschatological dimensions of time and history, including their approach to the future, taking the Bible and the thoughts of certain Christian thinkers as a point of reference. The relationship between the history of salvation and secular history has been especially accentuated. Philosophical considerations on history in Christianity have been intertwined with thoughts about the future in eschatological context.